Pengaruh Kepemilikan Institusional, Profitabilitas, dan Leverage Terhadap Nilai Perusahaan - Mutiara Paramastri; Tri Hesti Utaminingtyas; Muhammad Yusuf (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to examine whether institutional ownership, profitability, and leverage have an effect on firm value. The population in this study consists of companies in the financial sector for the period 2021 to 2022. The sample size for this study includes 94 companies, with a total of 188 observations. The sampling technique employed is purposive sampling. The research method used is quantitative, with secondary data as the data source. Data analysis is conducted using data panel regression analysis with eviews version 12. The results of this research provide empirical evidence that institutional ownership and profitability have no effect on company value. Meanwhile, leverage has a positive effect on company value.